Impact of stimulation duration and gonadotropin type on the incidence of premature progesterone elevation – a retrospective analysis of the Ensure data. (2nd December 2018) - Lawrenz, Barbara; Long, Jianmin; Stoop, Dominic; Missou, Irine; Fatemi, Human
Abstract: Elevated progesterone levels on the day of trigger negatively impact the outcome of assisted reproductive technique (ART) treatment and forced ovarian stimulation might be a cause of progesterone elevation during ovarian stimulation. To analyze the impact of forced and prolonged stimulation on the progesterone elevation, this data analysis from the Ensure study compared hormonal stimulation with corifollitropin alpha (CFA)-only with CFA plus recombinant (rec) follicle-stimulating hormone (FSH) after day 8 (CFA-plus group) of ovarian stimulation. In the Ensure study, 268 patients underwent ovarian stimulation with 100 µg CFA and 128 patients with recombinant FSH. A total of 35 patients (13.1%) from the CFA-arm received the hCG trigger after stimulation with CFA-only, 233 patients (86.9%) needed additional rec FSH from day 8 onwards to meet the criteria for trigger. Progesterone levels >0.8 ng/ml on the trigger day occurred in 90 patients (38.6%) from the CFA plus FSH group and only in one patient (2.8%) in the CFA-only group ( p < .001). The ongoing pregnancy rate (OPR) was 31.4% (11/35) for patients in the CFA-only group and 24.5% (57/233) for patients CFA-plus group with additional recFSH after day 8 ( p = .378). This set of data demonstrates that prolongation of stimulation in combination with intense stimulation leads to a statistically significant increased incidence of progesterone elevation on the day of trigger. 摘要: 诱发当天孕酮水平升高对辅助生殖技术（ART）的结果产生负面影响, 强的卵巢刺激可能是卵巢刺激过程中孕酮过早升高的原因。为了分析强的和长时间刺激对孕酮升高的影响, 来自Ensure研究的数据对卵巢刺激第8天后单用卵泡刺激素a进行刺激（CFA组）、与用CFA+重组（rec）卵泡刺激素（FSH）进行激素刺激（ CFA-plus组）进行了分析比较。在Ensure研究中, 268名患者接受了100μg CFA的卵巢刺激, 128名患者接受了重组FSH的卵巢刺激。来自CFA组的总共35名患者（13.1％）在单用CFA刺激后接受hCG诱发, 233名患者（86.9％）从第8天开始需要额外的rec FSH以满足诱发标准。CFA-plus组的90名患者（38.6％）和CFA组中仅一名患者（2.8％）出现了诱发日的孕酮水平> 0.8 ng/ml（p <.001）。CFA组的持续妊娠率（OPR）为31.4％（11/35）, 在第8天后增加rec FSH的CFA-plus组的持续妊娠率（OPR）为24.5％（57/233）（p = .378）。这组数据表明, 刺激时间延长与强烈刺激相结合, 导致触发当天孕酮升高的发生率显著增加, 具有统计学意义。